Visualization of Intermittent Splash with Gas Blowing from a Top Lance – Breakup of Cavity Surface Causing Intermittent Splash - Sato, Shingo; Okada, Jun; Ueda, Yoshiaki; Iguchi, Manabu (ISIJ International, 2020)
This study aims to visualize an instantaneous event of intermittent splashing from a bath surface caused by gas blowing from a top lance. The visualization techniques include computational fluid dynamics (CFD) and an experimental procedure using a high-speed camera. A remarkable finding is the fact that the difference between the air pressure inside the cavity and hydrostatic pressure outside the cavity forms a constriction and causes a strong intermittent splash.